ANALISIS MANAJEMEN RISIKO PENDISTRIBUSIAN ZAKAT PADA LAZNAS DAARUT TAUHIID PEDULI CABANG MALANG - Ismiyatun Nafi'ah; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The purpose of this researchis to find out the risk management of zakat distribution carried out by laznas Daarut Tauhiid Peduli Malang can increase the utilization of zakat.The method used in this research is an explanatory qualitative approach. The choice of the main focus in this research was based on the fact that the most impactful risk is the risk of misdirection (distribution) or inefficiency, so it will potentially decrease the reputation and trust of muzakki towards amil zakat institutions. The results of this research there are three points that are considered capable to influence the distribution of zakat such as dishonesty of prospective beneficiaries, inconsistent mustahik in giving reports, and the behavior of mustahik is not good. During the implementation, Daarut Tauhiid Peduli Malang can manage distribution risk so that it can increase the utilization of zakat.Keywords: zakat, risk management, risk of zakat distribution, increased utilization of zakat, laznas Daarut Tauhiid Peduli Malang